2023
DOI: 10.3390/genes14051052
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA TRHDE-AS1 Correlated with Genomic Landscape and Clinical Outcome in Glioma

Abstract: The role of lncRNA in cancer development has received more and more attention in research. A variety of lncRNAs are associated with the occurrence and development of glioma. However, the role of TRHDE-AS1 in glioma is still unknown. In this study, we explored the role of TRHDE-AS1 in glioma through bioinformatic methods. We first identified an association between TRHDE-AS1 and tumor prognosis in pan-cancer analysis. Subsequently, the expression levels of TRHDE-AS1 in various clinical types of glioma were compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Another study investigated the relationship between the lncRNA TRHDE-AS1 and the development of gliomas. The prognostic analysis, differential expression analysis, potential pathway mechanism analysis, mutation analysis and immune infiltration analysis of the expressed genes indicated that this lncRNA has great potential in guiding clinical prognosis prediction and future therapeutic decisions ( 21 ). According to database analysis, INHA is a diagnostic and prognostic marker for LUAD, and high expression of this molecule is a risk factor for a poor prognosis in LUAD patients and promotes LUAD cell proliferation and invasion in vitro and in vivo by activating the EGFR pathway ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another study investigated the relationship between the lncRNA TRHDE-AS1 and the development of gliomas. The prognostic analysis, differential expression analysis, potential pathway mechanism analysis, mutation analysis and immune infiltration analysis of the expressed genes indicated that this lncRNA has great potential in guiding clinical prognosis prediction and future therapeutic decisions ( 21 ). According to database analysis, INHA is a diagnostic and prognostic marker for LUAD, and high expression of this molecule is a risk factor for a poor prognosis in LUAD patients and promotes LUAD cell proliferation and invasion in vitro and in vivo by activating the EGFR pathway ( 22 ).…”
Section: Discussionmentioning
confidence: 99%